2016
DOI: 10.1016/j.pscychresns.2016.08.004
|View full text |Cite
|
Sign up to set email alerts
|

White matter structure in the uncinate fasciculus: Implications for socio-affective deficits in Autism Spectrum Disorder

Abstract: a b s t r a c tIndividuals with Autism Spectrum Disorder (ASD) have social and communication deficits and difficulties regulating emotions. The brain bases of these socio-affective deficits are not yet clear, but one candidate is structural connectivity in the left uncinate fasciculus, which connects limbic temporal and frontal areas thought to be involved in socio-affective processing. In this study, we assessed white matter structure in the left and right uncinate fasciculus in 18 high-functioning individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 57 publications
6
17
0
Order By: Relevance
“…More than half of these studies included participants with ASD who had average cognitive capacity overall, whilst other studies either included individuals with lower cognitive capacity or did not provide information regarding participants' cognitive function. Poor ER may be inherent in ASD [Mazefsky et al, ; Mazefsky & White, ], and recent evidence supports this view [e.g., Konstantareas & Stewart, ; Nader‐Grosbois & Mazzone, ; Pitskel, Bolling, Kaiser, Pelphrey, & Crowley, ; Richey et al, ; Samson et al, ; Samson et al, ]. All ASD core symptoms have been shown to be linked to emotion dysregulation [Berkovits, Eisenhower, & Blacher, 2017], with restricted and repetitive behaviors, interests, and activities being the strongest predictor [Samson et al, ].…”
Section: Emotion Regulation In Asdmentioning
confidence: 99%
See 1 more Smart Citation
“…More than half of these studies included participants with ASD who had average cognitive capacity overall, whilst other studies either included individuals with lower cognitive capacity or did not provide information regarding participants' cognitive function. Poor ER may be inherent in ASD [Mazefsky et al, ; Mazefsky & White, ], and recent evidence supports this view [e.g., Konstantareas & Stewart, ; Nader‐Grosbois & Mazzone, ; Pitskel, Bolling, Kaiser, Pelphrey, & Crowley, ; Richey et al, ; Samson et al, ; Samson et al, ]. All ASD core symptoms have been shown to be linked to emotion dysregulation [Berkovits, Eisenhower, & Blacher, 2017], with restricted and repetitive behaviors, interests, and activities being the strongest predictor [Samson et al, ].…”
Section: Emotion Regulation In Asdmentioning
confidence: 99%
“…Secondly, these regions show atypical patterns of activation in ASD across a range of executive function tasks [Minshew & Keller, 2010; Schmitz et al, ; Shafritz, Dichter, Baranek, & Belger, ; Kana, Keller, Minshew, & Just, ], which may explain the deficits in cognitive reappraisal observed in ASD. Finally, research has shown there is less connectivity between frontal regions and the lower limbic brain in individuals with ASD [Samson et al, ], and during tasks involving down‐regulation of negative emotions, there is decreased engagement of prefrontal regions and lack of amygdala down‐regulation in ASD [Pitskel et al, ; Richley et al 2015]. It is apparent that these two separate streams of neurological research, one examining executive function and the other emotion regulation, are largely related.…”
Section: Emotion Regulation Interaction and Flexibility: A New Approamentioning
confidence: 99%
“…The decreased density of OFC neurons and axons in adults with ASD observed in our study, provides evidence for parallel development of pathology in amygdala and OFC in ASD. This is also supported by functional studies that showed reduced amygdala-OFC activity in adults with ASD [65], and structural studies that showed reduced tract volume and lower mean fractional anisotropy values in the uncinate fasciculus, the axon bundle connecting OFC and the temporal lobe, including the amygdala [28,29,89].…”
Section: Discussionmentioning
confidence: 57%
“…Further, FA in the UF correlated with therapy duration and clinical outcome as measured by the Child Autism Rating Scale ( 74 ). Samson et al ( 75 ) assessed WM alteration in 18 ASD group and typically developed (TD) controls, and investigated the relationship between FA in UF using DTI and socio-affective deficit. They reported that ASD group had lower FA in left UF than TD, and within ASD group, FA was related to socio-affective deficit ( 75 ).…”
Section: Discussionmentioning
confidence: 99%
“…Samson et al ( 75 ) assessed WM alteration in 18 ASD group and typically developed (TD) controls, and investigated the relationship between FA in UF using DTI and socio-affective deficit. They reported that ASD group had lower FA in left UF than TD, and within ASD group, FA was related to socio-affective deficit ( 75 ). These results would support the correlation between AQ representing autistic traits and UF features in the current study, but it would be difficult to evaluate whether our subjects had socio-emotional deficits without functional data of socio-emotional function.…”
Section: Discussionmentioning
confidence: 99%